Church in Diaspora as a factor in the preservation of historical memory of Ukrainians - Georgii Fylypovych (Українське Pелігієзнавство, 2016)
Georgiy Fylypovych. Church in Diaspora as a factor in the preservation of historical memory of Ukrainians. The article analyzes the role of the Church in the formation and preservation of historical memory in the Ukrainian Diaspora. It turns out the influence of churches on national identity through the creation of autonomous image of Ukraine and Ukrainians, positive stereotypes and myths, scientific concepts and popular brands.